2019
DOI: 10.1038/s41598-019-51444-x
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic structure of Mycoplasma ovipneumoniae informs pathogen spillover dynamics between domestic and wild Caprinae in the western United States

Abstract: Spillover diseases have significant consequences for human and animal health, as well as wildlife conservation. We examined spillover and transmission of the pneumonia-associated bacterium Mycoplasma ovipneumoniae in domestic sheep, domestic goats, bighorn sheep, and mountain goats across the western United States using 594 isolates, collected from 1984 to 2017. Our results indicate high genetic diversity of M. ovipneumoniae strains within domestic sheep, whereas only one or a few strains tend to circulate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 77 publications
3
69
1
Order By: Relevance
“…None of the other juvenile mortalities from BSP (n = 1) or TCS (n = 1) tested positive for M. ovipneumoniae. The M. ovipneumoniae strain-type of the samples collected from the BHP and RSP juveniles matched the straintype (NV_BHS_SantaRosas_2651_2014_4; Kamath et al, 2019) of all the other previously strain-typed bighorn sheep at the available sequences from the Santa Rosa meta-population and Rattlesnake population (Table S13).…”
Section: Pregnancy Rates and Observation Of Juvenile Bighorn Sheepmentioning
confidence: 67%
See 1 more Smart Citation
“…None of the other juvenile mortalities from BSP (n = 1) or TCS (n = 1) tested positive for M. ovipneumoniae. The M. ovipneumoniae strain-type of the samples collected from the BHP and RSP juveniles matched the straintype (NV_BHS_SantaRosas_2651_2014_4; Kamath et al, 2019) of all the other previously strain-typed bighorn sheep at the available sequences from the Santa Rosa meta-population and Rattlesnake population (Table S13).…”
Section: Pregnancy Rates and Observation Of Juvenile Bighorn Sheepmentioning
confidence: 67%
“…Considerable variation has been observed in levels of all-age mortality at first contact, subsequent adult survival, and juvenile survival in following years among populations and across evolutionary lineages and habitats ( Cassirer et al, 2018 ; Dekelaita et al, 2020 ). That variation has been hypothesized to stem from numerous causes, including strain virulence ( Kamath et al, 2019 ), nutritional factors such as forage quality and population density ( Dekelaita et al, 2020 ), stochastic factors such as the presence of chronic carriers ( Cassirer et al, 2018 ; Garwood et al, 2020 ), genetic diversity of host populations ( Cassirer et al, 2018 ), and phenological differences resulting in different patterns of aggregation, contact, and dispersal ( Cassirer et al, 2018 ). Indeed, bighorn sheep inhabit ecosystems ranging from the arid deserts of northern Mexico and the southwestern United States of America to the frigid northern Rocky Mountains of Alberta and exhibit significant phenotypic variation and evidence of local adaptation ( Wehausen & Ramey II, 2000 ; Wiedmann & Sargeant, 2014 ; Malaney et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found 11 intermittent carriers in our control population but none in our treatment population (Table 1). Strain typing of samples from intermittent carriers in the control population revealed that eight changed from noncarriers to carriers when infected with a strain previously found in bighorn sheep in Deadwood, South Dakota and western Nebraska (Kamath et al, 2019). These individuals therefore were not intermittently carrying a single strain of Mo .…”
Section: Discussionmentioning
confidence: 88%
“…Based on strain typing data, adult bighorns in the Spring Creek subherd were exposed to an introduced strain sometime between 14 November 2016 and 13 December 2016. We therefore set time of exposure to the introduced strain in Spring Creek at the midpoint between those dates and coded strain type exposure as binary and time‐varying (exposure to introduced strain BHS‐043 = 1, exposure to resident strain BHS‐058 = 0; Kamath, Manlove, Cassirer, Cross, & Besser, 2019). All adults outside the Spring Creek subherd were modeled as only exposed to the resident strain (BHS‐058) for the duration of the study.…”
Section: Methodsmentioning
confidence: 99%
“…With the absence of ecological and/or phylogenetic barriers, parasites are more likely to expand their host range resulting in zoonotic diseases, such as those spilling over into humans from rodent or bat reservoirs (Han et al 2015, Morens et al 2020) or from contact with domesticated animals (Woolhouse et al 2001). Due to the potential fitness consequences of host switches to novel hosts (Liu et al 2010, Kamath et al 2019), it is important to understand the specificity with which parasite species infect their hosts and the contribution of host phylogenic relatedness and environmental factors to the membership of parasite species in ecological communities. The ecological and evolutionary constraints of specialization result in a trade‐off in which host generalists may achieve broader geographic distributions through the parasitism of many different host species (Medeiros et al 2014), whereas host specialist parasites may achieve higher infection rates by maximizing resource acquisition and immune evasion within co‐evolved host species (Longdon et al 2014, Poulin and Morand 2014).…”
Section: Introductionmentioning
confidence: 99%